2012
DOI: 10.1186/1472-6882-12-241
|View full text |Cite
|
Sign up to set email alerts
|

Differential proteomics analysis of the analgesic effect of electroacupuncture intervention in the hippocampus following neuropathic pain in rats

Abstract: BackgroundEvidence is building steadily on the effectiveness of acupuncture therapy in pain relief and repeated acupuncture-induced pain relief is accompanied by improvement of hippocampal neural synaptic plasticity. To further test the cellular and molecular changes underlying analgesic effect of acupuncture, the global change of acupuncture associated protein profiles in the hippocampus under neuropathic pain condition was profiled.MethodsThe chronic constrictive injury (CCI) model was established by ligatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 44 publications
1
16
0
Order By: Relevance
“…We found that after CCI, MEK1 was down-regulated in the hippocampus and up-regulated in the hypothalamus. However, following 12 sessions of EA intervention, MEK1 in both regions recovered to normal levels [18, 21]. We extended that work in the present study to clarify the differential effects of multiple and single EA intervention sessions in CCI rats.…”
Section: Introductionsupporting
confidence: 65%
See 2 more Smart Citations
“…We found that after CCI, MEK1 was down-regulated in the hippocampus and up-regulated in the hypothalamus. However, following 12 sessions of EA intervention, MEK1 in both regions recovered to normal levels [18, 21]. We extended that work in the present study to clarify the differential effects of multiple and single EA intervention sessions in CCI rats.…”
Section: Introductionsupporting
confidence: 65%
“…ST36 is located 5 mm beneath the capitulum fibulae and lateral posterior to the knee joint, and GB34 is approximately 5 mm superior-lateral to ST36 [18]. In the present study, the animals in the EA group were treated with bilateral ST36 and GB34.…”
Section: Methodsmentioning
confidence: 92%
See 1 more Smart Citation
“…A 20 sec limit was imposed to prevent tissue damage. Each rat was assessed five times and the mean value was expressed as the thermal withdrawal latency (22). The paw withdrawal response to mechanical stimuli was measured using the Electronic von Frey Anesthesiometer (IITC Life Science Inc.).…”
Section: Methodsmentioning
confidence: 99%
“…In our previous studies, repeated EA intervention induces a cumulative effect in chronic constriction injury (CCI) rats [1820]. The analgesic effect of EA peaked after several successive sessions of treatment.…”
Section: Introductionmentioning
confidence: 99%